Food Cue Reactivity in Food Addiction: a Functional Magnetic Resonance Imaging Study - Schulte, Erica M. (Physiol Behav, 2019)
BACKGROUND: While neuroimaging studies have revealed that reward dysfunction may similarly contribute to obesity and addiction, no prior studies have examined neural responses in individuals who meet the “clinical” food addiction phenotype. METHODS: Women (n=44) with overweight and obesity, nearly half of whom (n=20) met criteria for moderate-to-severe Yale Food Addiction Scale 2.0 (YFAS 2.0) food addiction, participated in a functional magnetic resonance imaging cue reactivity task. Participants viewed images of highly processed foods, minimally processed foods, and household objects while thinking about how much they wanted each item. Differences in neural responses by YFAS 2.0 food addiction to highly processed and minimally processed food cues were investigated. RESULTS: There was a significant interaction between participant group and neural response in the right superior frontal gyrus to highly versus minimally processed food cues (r=.57). Individuals with YFAS 2.0 food addiction exhibited modest, elevated responses in the superior frontal gyrus for highly processed food images and more robust, decreased activations for minimally processed food cues, whereas participants in the control group showed the opposite responses in this region. Across all participants, the household items elicited greater activation than the food cues in regions associated with interoceptive awareness and visuospatial attention (e.g., insula, inferior frontal gyrus, inferior parietal lobe). CONCLUSIONS: Women with overweight or obesity and YFAS 2.0 food addiction, compared to those with only overweight or obesity, exhibited differential responses to highly and minimally processed food cues in a region previously associated with cue-induced craving in persons with a substance-use disorder. Overall, the present work provides further support for the utility of the food addiction phenotype within overweight and obesity.